2013
DOI: 10.1007/s40519-013-0054-7
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in food craving among overweight and obese patients attending low energy diet therapy: a matched case–control study

Abstract: This case-control study examined gender differences in food craving among a sample of overweight and obese patients attending low energy diet therapy. To disentangle the specific role of gender from the role of confounders, we paired groups for BMI, age and severity of binge eating as assed by the Binge Eating Scale (BES). The participants were 73 pairs of patients who were attending low energy diet therapy. All the participants were administered the State and Trait Food Cravings Questionnaire, trait version (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 72 publications
2
18
0
Order By: Relevance
“…Although the other situations assessed (e.g., kitchen or bakery) did not produce statistically significant differences of this kind after Bonferroni adjustment, there was a tendency for women to report more craving than men. Similarly, some other studies have found that females show higher reactivity than males, despite comparable severity of binge eating and BMI (Imperatori et al, 2013;Lafay et al, 2001;Núñez-Navarro et al, 2012). Given these results, future research should seek to recruit samples with larger numbers of men in order to obtain more conclusive data regarding gender differences.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Although the other situations assessed (e.g., kitchen or bakery) did not produce statistically significant differences of this kind after Bonferroni adjustment, there was a tendency for women to report more craving than men. Similarly, some other studies have found that females show higher reactivity than males, despite comparable severity of binge eating and BMI (Imperatori et al, 2013;Lafay et al, 2001;Núñez-Navarro et al, 2012). Given these results, future research should seek to recruit samples with larger numbers of men in order to obtain more conclusive data regarding gender differences.…”
Section: Discussionmentioning
confidence: 67%
“…Some studies have found significant differences according to gender (Imperatori et al, 2013;Lafay et al, 2001), with the incidence of food cravings being greater among women. With regard to age, it has been reported that the frequency of food cravings seems to decline as subjects grow older (Pelchat, 1997(Pelchat, , 2002.…”
Section: Other Related Characteristicsmentioning
confidence: 99%
“…It has been observed that women report higher levels of craving than men (Cepeda-Benito et al, 2003). In addition, obese and overweight female patients attending a low calorie diet therapy experienced more cravings for food than their male pairs (Imperatori et al, 2013). Finally, food cravings fully mediated the inverse relationship between rigid control strategies and dieting success (Meule et al, 2011) and it has been observed that chronic food restriction can trigger the desire to eat, even in the absence of hunger (Pelchat and Schaefer, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Another recent study found that females who were obese/overweight were more likely to experience cravings than males despite comparable binge eating severity 27 . Our hypothesis of gender moderation was only partially supported, though it does corroborate prior work suggesting significantly higher associations between general food cravings, chocolate cravings, and eating disorder psychopathology for females 10,28 .…”
Section: Discussionmentioning
confidence: 95%
“…The prevalence estimates for binge eating and BED (recurrent episodes of binge eating associated with marked distress and without regular compensatory behaviors 3 ), are approximately 4.9-11.2% and 3.6%, respectively, for women and 4.0-7.5% and 2.1%, respectively, for males 22-24 . While researchers have found that there are few differences in distal antecedents (e.g., age at first overweight, age at first diet, weight cycling) of binge eating by gender 25,26 , only a few studies have examined gender differences of more proximal correlates of binge eating such as food cravings 10,12,27 . In a recently published study comparing chocolate cravings in undergraduate men and women, male chocolate cravers had significantly fewer symptoms of eating disorders compared to male non-cravers 28 .…”
Section: Introductionmentioning
confidence: 99%